Prolegomena to a Social History of the Volscian History - Manneke, Mary Kathleen (My University, 1982)
The purpose of this thesis is to explore and examine the history and culture of the Volscian tribe in central Italy over a period of approximately 1000 years, from its appearance in the Italic peninsula in the Iron Age to the first century B.C. Using ancient literary sources, modern historical theory and analysis and archaeological evidence, the culture, language and social development of the Volscl is studied in detail from the fifth century to the decade following the Social War (91-87 B.C.), at which time the Volscian identity disappeared with the acquisition of Roman citizenship. Particular attention is paid to the settlement patterns of the Volscians in the Trerus and Liris river valleys, and the possibility of a chain of fortification centres in the fifth century is suggested. The improvement of this chain by the Romans into a communications network of intervisible forts and garrisons during the Volscian conquest of the fourth century, and later during the Samnite wars, is also investigated.
Keywords: Classics; Classics